Teacher Formation in the Mathematical Thinking through Problem Solving in the Second Phase of the CCyM Network of Reading Comprehension and Mathematics - López, Luz Stella; Universidad del Norte (Pontificia Universidad Javeriana, 2007)
This article shares the design, implementation, and evaluation of the Lesson Study process used for the professional development of teachers of mathematics, through the Red de Comprensión Lectora y Matemáticas – CCyM Network, in ways to teach mathematics through problem solving. The program began with a course on the implementation of the Thinking Classroom, followed by the semi-presencial Lesson Study process. An analysis of teacher interactions during the Lesson Study process yielded these categories of study: Group Collective Thinking, Mathematical Pedagogical Content Knowledge, Subject Matter Knowledge, Knowledge about Technology, and Expert Support. The analysis reflected variations in group interactions, in the command of concepts, in reflective practice, in the ability to make arguments and to propose changes in practice, and in the ability to self-regulate